Coptotermes sp. Termite Attacks in Some Locations of Red Meranti (Shorea leprosula Miq.) Plantation - ., Ngatiman; Fernandes, Andrian (KnE Life Sciences, 2017)
Red Meranti (Shorea leprosula Miq.) have been widely planted in secondary forests and logged over forest. Problems were found in the field is due to the presence of Coptotermes sp. termite attack in S. leprosula plants resulting to its death. The aims of this study were to determine the percentage and intensity of Coptotermes sp. termite attack. The method used is to perform observations of termite attack in several locations planting, i.e. in KHDTK Samboja (East Kalimantan), KHDTK Sebulu (East Kalimantan), PT INHUTANI II, Pulau Laut (South Kalimantan) and PT Suka Jaya Makmur (West Kalimantan). The results showed that the percentage and intensity of Coptotermes sp. termite attacks in KHDTK Samboja, respectively 7.3 % and 4.7 %, in KHDTK Sebulu 11.3 % and 8.2 %, in Inhutani II 5.8 % and 5.3 % and in PT Suka Jaya Makmur 5.4 % and 4.8 %. The source of termite attacks in plants in KHDTK Samboja and KHDTK Sebulu was the termite nest contained in secondary forest bordering S. leprosula plantations while the source of the termite attack in plants in Inhutani II and PT Suka Jaya Makmur was the termite nests located between S. leprosula plantations. Finally, Coptotermes sp termite attack disturbed S. leprosula plantation. Keywords: Coptotermes sp. termite attack; intensity termite attack; percentage termite attack; Shorea leprosula Miq.